Edukasi Sadar Bising Sebagai Upaya Promotif dan Preventif Terhadap Gangguan Dengar Melalui Media Podcast - Eka Arie Yuliyani; Hamsu Kadriyan; Mochammad Alfian Sulaksana; Faisal Libryan; Dewa Agung Istri Sintha Prajnyaswari; Baiq Ghassani Kayla; Andhito Rafid Chusaeri (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Advances in technology and communication media that are increasingly rapidly giving meaning to the development of education where various information can be easily accessed, including health. Among the various latest trends that have emerged, podcasts appear as a very interesting technology for conducting health education and can be accepted by all circles, including the millennial generation. Various health education themes have been carried out through podcasts, one of which is noise awareness which reviews various information about the importance of maintaining hearing health and its impact on quality of life. The millennial generation is an age group that is close to technological developments, so that more and more young people are at risk of hearing loss due to frequent exposure to loud sounds from gadgets or from a noisy surrounding environment. The results of this podcast recording are then uploaded through the YouTube channel with the hope that the information that has been reviewed in it will be able to increase high awareness of individuals, especially the younger generation regarding their daily attitudes in maintaining hearing health, as a preventive and promotive effort. The result of this activity is the acceptance of education about noise awareness by the public which can be seen from the viewers listed on the youtube page. There are 675 viewers on this podcast upload.